2018
DOI: 10.3390/ma11101881
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Enrichment Properties of Magnetic Dodecyl Chitosan/Silica Composite for Emerging Bisphenol Contaminants

Abstract: Magnetic dodecyl chitosan/silica composite was synthesized and characterized for the enrichment of emerging bisphenol contaminants. The result demonstrated that bispehnol A, bisphenol AF, bisphenol F, and bisphenol S can be efficiently extracted via the resulting composite from aqueous solution. The adsorption rate of four investigated bisphenols on the resulting composite was achieved in the range of 87–99% within 15 min. Bispehnol A was taken as a representative adsorbate to investigate the adsorption studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The porous polycalix [4]arenes can be regenerated several times through a simple cleaning procedure, while its performance remains basically unchanged and its energy consumption is lower than that required by activated carbon. Hu, Liu, Liu, Wu, and Zhang (2018) synthesized magnetic dodecyl chitosan/silica composites and studied their adsorption properties for bisphenol pollutants in aqueous solution. The results showed that in 15 min, 87%-99% of bisphenol A, bisphenol AF, bisphenol F, and bisphenol S in aqueous solution can be adsorbed by this composite.…”
Section: Othermentioning
confidence: 99%
“…The porous polycalix [4]arenes can be regenerated several times through a simple cleaning procedure, while its performance remains basically unchanged and its energy consumption is lower than that required by activated carbon. Hu, Liu, Liu, Wu, and Zhang (2018) synthesized magnetic dodecyl chitosan/silica composites and studied their adsorption properties for bisphenol pollutants in aqueous solution. The results showed that in 15 min, 87%-99% of bisphenol A, bisphenol AF, bisphenol F, and bisphenol S in aqueous solution can be adsorbed by this composite.…”
Section: Othermentioning
confidence: 99%